Promoting Internship Excellence: Key Strategies Employed by Pharmacy Schools for Successful Development - Hatem NAH (Dove Medical Press, 2023)
Najmaddin AH Hatem Department of Clinical Pharmacy, College of Clinical Pharmacy, Hodeidah University, Al-Hudaydah, YemenCorrespondence: Najmaddin AH Hatem, Department of Clinical Pharmacy, College of Clinical Pharmacy, Hodeidah University, P.O. 3114, Al-Hudaydah, Yemen, Tel +967 775040472, Email clin.pharm.najmaddin@gmail.comAbstract: Various early pharmacy practice experiences, such as introductory, advanced, and postgraduate internship programs, are part of the journey of future pharmacists during their educational experience in pharmacy schools. Pharmacy schools have the potential to enhance the quality of their internship programs by establishing strategies to provide comprehensive instruction and practical experience for students. Hence, this commentary shade light on the critical tactics employed by pharmacy schools to guarantee the growth and success of pharmacy students during their different internship programs.Keywords: pharmacy students, pharmacy schools, internship, pharmacy practice, residency, strategies